Visible Light Induced Photocatalytic Activity of Polyaniline Modified TiO2 and Clay-TiO2 Composites - K. P. Sandhya; Suja Haridas; S. Sugunan (Bulletin of Chemical Reaction Engineering & Catalysis, 2013)
Sonochemical synthesis of Titania, Titania-Polyaniline, and Clay-Titania-Polyaniline composites were car-ried out. The composite systems were characterized by various physico-chemical techniques. Photocatalytic activity was tested selecting some common dyes as substrates. Composites exhibited higher activity for the degradation of dyes under visible light in most of the cases. © 2013 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)